Digitalisasi Kegiatan Seni Budaya Sanggar Seni Topeng Malang Asmorobangun dalam Media Sosial Sebagai Sarana Peningkatan Pelestarian Budaya - Ayu Wulan, Diah; Edy Nur Widyaningsih, Galih; Goeyardi, Wandayani; Sonya Azarena, Alliya; Fadilatus Sa'diyah, Faiza; Sacalaros, Davida Diandra; Fathir, Ervin Nurul; Atifah, Naiya Salsabilla (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
The act of community service in 2024 arranged by a Chinese Literature major will be held in Sanggar Seni Topeng Malangan Asmorobangun. This studio was founded in the 1900 in order to conserve Tari Topeng Malangan. This studio also has dance, musical and musical practice activities and mask making training every week. From the activities at the Sanggar Seni Topeng Malangan, the study program wants to carry out service in accordance with the SDGs set by BAPPENAS by digitizing artwork and Malangan mask performances on YouTube social media. With digitalization, it is hoped that the cultural art activities of Topeng Malangan in Sanggar Seni Topeng Malangan Asmorobangun will gain broader recognition domestically and internationally. Furthermore, this program supports digital education and provides a platform for the youth to innovate in preserving the nation’s cultural heritage through social media. In consequence from these circumstances, this act of community service is required to be performed in order to instigate and resolve these problems: How is the digitalization of art and culture in Sanggar Seni Topeng Malangan Asmorobangun?